Visceral Fat Accumulation Is Related to Impaired Pancreatic Blood Perfusion and Beta-Cell Dysfunction in Obese Women - Szotkowská, Radka; Gojda, Jan; Plíhalová, Andrea; Weichet, Jiří; Potočková, Jana; Havlík, Jan; Polák, Jan; Anděl, Michal (Annals of nutrition & metabolism, 2021)
AIMS/HYPOTHESIS: Beta-cell failure plays a fundamental role in type 2 diabetes mellitus (T2DM) development. It has been shown that the beta-cells are among the most sensitive to hypoxia. We aimed to analyze whether decrease in pancreatic perfusion relates to 1/decline in beta-cell function and 2/visceral fat accumulation in patients with T2DM. METHODS: Fifteen women with T2DM on metformin therapy alone and fifteen women of comparable age and BMI without prediabetes/diabetes were cross-sectionally examined: clinical and anthropometric examination, fast sampled intravenous glucose tolerance test (FSIVGTT), dynamic contrast-enhanced magnetic resonance imaging to assess pancreatic perfusion (area under the curve of postcontrast saturation, AUCTSIC), and visceral adiposity (VAT, calculated from transverse sections at the level L2-L5 vertebrae). RESULTS: Pancreatic blood perfusion (AUCTSIC) did not differ between groups (p = 0.273), but it negatively correlated with BMI (r = -0.434, p = 0.017), WHR (r = -0.411, p = 0.024), and VAT (r = -0.436, p = 0.016) in both groups. Moreover, AUCTSIC in the head of the pancreas negatively correlated with the level of fasting glycemia (r = -0.401, p = 0.028) and HOMA-IR (r = -0.376, p = 0.041). DISCUSSION/CONCLUSION: We showed that decreased pancreatic perfusion did not relate to beta-cell dysfunction in early stages of T2DM development, but it was related to VAT, insulin resistance, and higher fasting glycemia. Furthermore, lower pancreatic perfusion was related to VAT, insulin resistance, and higher fasting glycemia.
Keywords: obezita; Humans; index tělesné hmotnosti; Body Mass Index; Insulin Resistance; Intra-Abdominal Fat; Female; lidé; Blood Glucose; pankreas; Pancreas; Diabetes Mellitus, Type 2; Perfusion; Type 2 diabetes mellitus; ženské pohlaví; nitrobřišní tuk; inzulinová rezistence; Insulin; krevní glukóza; perfuze; Obesity; Blood perfusion; diabetes mellitus 2. typu; inzulin